Przestrzeń i społeczeństwo Chrzanowa średniowiecznego i nowożytnego - Żurek, Dorota (Księgarnia Akademicka Publishing, 2015)
SPACE AND SOCIETY IN THE MEDIEVAL AND EARLY MODERN CHRZANÓW The thesis concentrates on the sociotopography of the city of Chrzanów. During the period under consideration it was a small city situated in the Kraków Land on the border of Lesser Poland and Silesia. The choice of this city was dictated mainly by the existence of a considerably rich source material. The main part of the source material used for the research consists of the municipal records preserved and stored in the National Archive in Kraków. The collection is comprised of twenty three municipal record books, thirteen of which were thoroughly analysed. One of the records is referred to as the counciltribunal record, two are labelled as the record of the municipal council, and the remaining ten are the records of the municipal tribunal. Apart from the municipal records other sources were used for the research, mainly fragments of the guild records and the guild privileges, records of the episcopal visitations, tax registers, and – essential for the sociotopographical research – city maps from the nineteenth century, including the cadastral map form 1848. The year 1655 marks the end point of the period under consideration, while the starting point is not precisely indicated. The analysis of the spatial and social structures covers a period from the first half of the fifteenth century, but it was also necessary to outline the earlier history of the town, especially the period prior to the location act, and settle the question of the date and circumstances of the location itself. Unfortunately it was impossible to decisively solve the last mentioned problem.